2011
DOI: 10.1158/0008-5472.can-10-1660
|View full text |Cite
|
Sign up to set email alerts
|

VEGFR-1 Expressed by Malignant Melanoma-Initiating Cells Is Required for Tumor Growth

Abstract: Melanoma growth is driven by malignant melanoma-initiating cells (MMIC) identified by expression of the ATP-binding cassette (ABC) member ABCB5. ABCB5+ melanoma subpopulations have been shown to overexpress the vasculogenic differentiation markers CD144 (VE-cadherin) and TIE1 and are associated with CD31− vasculogenic mimicry (VM), an established biomarker associated with increased patient mortality. Here we identify a critical role for VEGFR-1 signaling in ABCB5+ MMIC-dependent VM and tumor growth. Global gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
161
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(173 citation statements)
references
References 44 publications
9
161
0
3
Order By: Relevance
“…Interestingly, CD271 and ABCB5 were recently found to be preferentially coexpressed on the same tumor subpopulation in clinical human melanoma specimens. 75 In another report, a rare subpopulation of melanoma cells identified by high aldehyde dehydrogenase (ALDH) activity displayed enhanced tumorigenicity and capacity for selfrenewal over ALDH-negative cells when serially transplanted into NOD/SCID and IL-2Rg À/À NOD/SCID mice. 76 The existence of a stem cell-like population in melanoma was additionally fortified by a recent study of the effect of the ECM glycoprotein tenascin-C on melanoma progression; these data demonstrated that tenascin-C in the microenvironment encouraged manifestation of a stem cell-like phenotype in melanoma cells that included the expression of ABCB5.…”
Section: Stochastic Model Cancer Stem Cell Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, CD271 and ABCB5 were recently found to be preferentially coexpressed on the same tumor subpopulation in clinical human melanoma specimens. 75 In another report, a rare subpopulation of melanoma cells identified by high aldehyde dehydrogenase (ALDH) activity displayed enhanced tumorigenicity and capacity for selfrenewal over ALDH-negative cells when serially transplanted into NOD/SCID and IL-2Rg À/À NOD/SCID mice. 76 The existence of a stem cell-like population in melanoma was additionally fortified by a recent study of the effect of the ECM glycoprotein tenascin-C on melanoma progression; these data demonstrated that tenascin-C in the microenvironment encouraged manifestation of a stem cell-like phenotype in melanoma cells that included the expression of ABCB5.…”
Section: Stochastic Model Cancer Stem Cell Modelmentioning
confidence: 99%
“…Moreover, such cells preferentially express vascular endothelial growth factor receptor-1 (VEGFR-1), which was shown via knockdown experimentation to be required for laminin production, VM, and efficient tumor growth in vivo. 75 The current model of signaling pathways involved in VM highlights the dynamic interaction between melanoma cells and their microenvironment. Primitive, aggressive melanoma cells that encourage VM upregulate several endothelialassociated genes, including VE-cadherin (CD144), the receptor protein tyrosine kinase erythropoietin-producing hepatocellular carcinoma-A2 (EphA2), and laminin 5 g2-chain, a major component of the basement membranes.…”
Section: How Primitive Melanoma Cells May Encourage 'Vasculogenic Mimmentioning
confidence: 99%
See 1 more Smart Citation
“…Further evidence correlating VEGFR-1 and the progression of disease was observed in patient-derived xenograft (PDX) models of melanoma, where VEGFR-1 expression on malignant tumor cells was associated with a more aggressive tumor-initiating cell population (25). Other studies with the CT26 colorectal cancer syngeneic mouse model showed that blockade of both VEGFR-1 and VEGFR-2 was required to prevent the vascularization and growth of micrometastases (26).…”
Section: Introductionmentioning
confidence: 99%
“…The study of tumor initiating cells provides a potential explanation of tumor aggressiveness, drug resistant and distant metastasis [1,2]. Several reports showed that CD133, CD20, CD271, ABCG2 and ABCB5 act as a potential marker to characterize CSCs in melanoma [3,4].…”
Section: Commentarymentioning
confidence: 99%